2017
DOI: 10.14814/phy2.13371
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation of initially vitamin D-deficient mice diminishes lung inflammation with limited effects on pulmonary epithelial integrity

Abstract: In disease settings, vitamin D may be important for maintaining optimal lung epithelial integrity and suppressing inflammation, but less is known of its effects prior to disease onset. Female BALB/c dams were fed a vitamin D3‐supplemented (2280 IU/kg, VitD+) or nonsupplemented (0 IU/kg, VitD−) diet from 3 weeks of age, and mated at 8 weeks of age. Male offspring were fed the same diet as their mother. Some offspring initially fed the VitD− diet were switched to a VitD+ diet from 8 weeks of age (VitD−/+). At 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
(166 reference statements)
1
20
0
Order By: Relevance
“…It is evident that as the metabolism of nutrients decreases with age ( 5 , 41 ), the VD 3 requirements should be reinvestigated in relation to stage of laying considering the impact of aging on VD 3 requirements and due to VD 3 and its metabolites playing a vital role in the uptake, deposition, and excretion of Ca ( 5 , 21 , 42 ). Likewise, other authors ( 5 , 24 , 27 ) showed similar findings. The VD 3 is essential for the formation of Ca-bound proteins, which are involved in the active transport of Ca across the intestine ( 28 ), and in lipoprotein, the precursor of yolk formation ( 5 , 20 , 21 ).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It is evident that as the metabolism of nutrients decreases with age ( 5 , 41 ), the VD 3 requirements should be reinvestigated in relation to stage of laying considering the impact of aging on VD 3 requirements and due to VD 3 and its metabolites playing a vital role in the uptake, deposition, and excretion of Ca ( 5 , 21 , 42 ). Likewise, other authors ( 5 , 24 , 27 ) showed similar findings. The VD 3 is essential for the formation of Ca-bound proteins, which are involved in the active transport of Ca across the intestine ( 28 ), and in lipoprotein, the precursor of yolk formation ( 5 , 20 , 21 ).…”
Section: Resultssupporting
confidence: 78%
“…The Ca-binding protein implicated in the active transport of Ca across the intestinal wall requires VD 3 ( 18 , 22 ). In the literature, VD 3 has many health, immunological, and physiological benefits ( 5 ), and it is a vital vitamin that plays a considerable role in the development of muscle, skeletal health, and in sustaining the homeostasis of calcium and phosphorus ( 18 , 23 , 24 ). Formation of eggshell and health of bone in laying hens is essential and involves the integration between the metabolism of Ca, P, and VD 3 ( 5 , 18 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…45 Other studies have proved that, in disease settings, vitamin D has positive effects on maintaining lung epithelial integrity and inhibiting inflammatory responses. 46,47 Vitamin D supplementation ameliorated pulmonary morphological alternations in LPS-induced bronchopulmonary dysplasia, inhibited IFN-γ overproduction and, thereby, suppressed inflammation. 48 Vitamin D was also confirmed to enhance the ability of neutrophils to kill Streptococcus pneumoniae and inhibit excessive inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies that have attempted to address the ability of VD3 supplementation after deficiency have yielded mixed results. While supplementation reduced eosinophil and neutrophil numbers in bronchoalverolar lavage [ 83 ], deficiency correction had only limited effect of improving epithelial integrity in the lung which was only modestly impacted by VD3 deficiency in otherwise healthy mice [ 84 ]. Collectively, these reports and our data highlight the need for additional research into how 25(OH)D3 deficiency and VD3 supplementation regulates local vitamin D metabolism and subsequent airway functions.…”
Section: Discussionmentioning
confidence: 99%